South Asian Muslim women on the move: missionaries in South Africa. Issue 2 (3rd July 2017) - Koch, Julia
ABSTRACT: Colonial migration and settlement rhythms entangle the shores and hinterlands of the Western Indian Ocean region religiously, economically, and socially until today. While historiographic and biographic studies are often centred on men in the late nineteenth and the twentieth centuries, this paper sheds light on current life worlds of South Asian women in a rural South African area. The women display religiosity in the midst of a generation gap between 'old' and 'new' Indians, 'locals' and 'foreigners', respectively. The paper attempts an analysis of transoceanic migration networks. This is necessary because the post-apartheid phenomenon of renewed Indian–South African relations questions notions of belonging. The ethnographic research focuses on South Asian Muslims, often from Gujarat or from what today is known as Pakistan. It teases out a deeper understanding of class-based, racially inflected Islamic practices within the configuration of global Muslim social relations.